THE EFFECT OF INTENSITY AND LONG EXPOSURE TO EXTREMELY LOW FREQUENCY (ELF) MAGNETIC FIELD ON DENSITY OF SILK TOFU - Nurul Mega Astutik; Sudarti Sudarti; Albertus Djoko Lesmono (Pendidikan Fisika UIN Alauddin Makassar, 2022)
This study aims to examine the effect of intensity and duration of exposure to the ELF magnetic field on the density of silken tofu. The type of research used is experimental research with Completely Randomized Design (CRD). The research sample consisted of 5 samples of the control group (without exposure to the ELF magnetic field) and 36 samples of the experimental group (exposed to ELF magnetic fields of 600µT, 900 T, and 1200 T for 50 minutes, 100 minutes, and 150 minutes). Measurement of research data was carried out at 0 hours before exposure and at 10, 20, 30, and 40 hours after exposure. The results showed that exposure to the ELF magnetic field could affect changes in the density value of silken tofu. This is evidenced by the graph of the density value in the control group measurement which decreased more sharply than the experimental group which tended to maintain the density value. The intensity of the ELF magnetic field which is effective in maintaining the density value of silken tofu is at 1200 µT with an exposure time of 100 minutes.